PERAN GENDER KOMITE AUDIT DALAM MEMODERASI HUBUNGAN TEKANAN, KESEMPATAN, RASIONALISASI, DAN KECURANGAN LAPORAN KEUANGAN - Bagaskara, Tri Cahyo; Chariri, Anis (Diponegoro Journal of Accounting, 2024)
This research aims to examine the relationship between fraud triangle theory and financial statement fraud. The independent variables in this research include external pressure, ineffective monitoring, and auditor change. Meanwhile, the dependent variable in this research is financial statement fraud, which is measured using dummy variables. Companies are classified into fraud and non-fraud companies based on the results of Altman Z-Score calculations. Apart from that, this research also tested the moderating variable, namely audit committee gender, which was analyzed using the MRA model.This research uses construction company objects listed on the Indonesia Stock Exchange during 2020–2022. Based on the purposive sampling method, 16 construction companies were obtained that met the criteria with a final sample size of 48 data. The relationship between the independent variable and the dependent variable was analyzed using the regression analysis.The statistical results of this research found a positive relationship between external pressure and auditor change on fraudulent financial reports. Meanwhile, ineffective monitoring have no influence on financial statement fraud. This research is also unable to prove that the gender of the Audit Committee moderates the relationship between external pressure, ineffective monitoring, and auditor change on fraudulent financial reports.